Analysis of Water Quality in the Mandaong River for Development of Freshwater Fish Cultivation - M. Abjan Fabanjo; Inayah Inayah (Jurnal Biologi Tropis, 2021)
The Mandaong River is a river flow that originates from the springs of Mount Sibela which until now has not been known with certainty the upstream point of the Mandaong River. This river flows through 3 (three) villages, namely Mandaong Village which is a downstream area, Makean Village Village and Papaloang Village which is an area of the Mandaong River body. Taking into account the position of the Mandaong River which flows from the mountains through plantations and settlements, it is estimated that it will receive some input from both natural processes and from the activities of the surrounding community such as bathing, washing, excavating sand, agriculture and settlements. Disposal of domestic waste, organic and inorganic waste so that there will be a decrease in the quality of river water in the form of physical, chemical and biological aspects. This study aims to determine the water quality of the Mandaong river based on physical, chemical and biological parameters and to determine the status of the water quality of the Mandaong river for the development of freshwater fish farming. The method of collecting water quality data on physical and chemical parameters was measured directly in the field and water samples were taken for further testing in the laboratory. For macroinvertebrate sampling by using nets /nets hand, the laying of nets is carried out systematically on the left, middle and right bank of the river at each predetermined station. Based on the results of measurements of the water temperature in the Mandaong river, it ranges from 25ÃÂ°CÃ¢â¬â27ÃÂ°C, Flow Speed ranges from 1.02Ã¢â¬â2.06, River depth ranges from 45Ã¢â¬â97 cm. and water pH ranged from 6.76-7.31, DO content ranged from 6.31-6.78, BOD content ranged from 0.10-5.63, nitrate content ranged from 0.361-2.068, phosphate content ranged from 4.506 Ã¢â¬â6.753, ammonia content in the range of 0.002, detergent content in the range of 50. Family Biotic Index (FBI) values ranged from 3.36-4.16. The FBI index value shows that the water quality of the Mandaong River is in the very good category with the level of pollution not polluted by organic matter at stations 1 and 2, while at station 3 it is in the very good category with a slightly polluted level of organic matter. Based on the results of research and discussion, it can be concluded from this study that the testing of physical, chemical and biological parameters in research on the Mandaong river shows that the level of river water pollution is included in the very good category. Therefore, the water quality of the Mandaong River can be developed for freshwater fish farming activities.